Analisis Potensi Wilayah Dharmasraya Untuk Pengembangan Sapi Potong dan Kaitannya Dengan Pemberdayaan Ekonomi Masyarakat - Ediset Ediset; E Heriyanto (Universitas Andalas, 2012)
The research was goals : 1) To be able Dharmasraya potency for developing beef cattle farming. 2) To be able existing condition attempt cattle live stock and the relationship means empowerment society economy. Approach research was secondary data analysis and survey. Sample all of cattle live stock which breeding cattle live stock intensively, taking sample by cluster random sampling. Respondent was choose by simple random sampling, primary data was collected by interview directly and questioner and secondary data collect from relevant agency. Then both of data were analyzed qualitative and quantitative. Proceed of research showed Dharmasraya has potency for developing cattle live stock could view from : 1) Aspect of natural resources region such as land available. 2) Region social culture aspect such as number of breeder, education of breeder and tradition of breeding of live stock. 3) Board aspect such as monetary, government administration, information and technology. Existing condition breed of live stock that indicated to empowerment society economy which viewed based on marketing aspect and absorbing employee. Based on proceed of researched we could concluded that Dharmasraya had good potent for developing live stock, and breed existing condition for cattle live stock that indicated for empowerment society economy.